The Relationship between Job Stress, Job Satisfaction, and Employee Performance: A study Among Hospital Employees of South Waziristan Tribal District in Pakistan - Dr.Mohammad Sohail Jan (Review Journal of Social Psychology & Social Works, 2024)
This study presents an extensive investigation into the connections between healthcare workers' levels of stress, job satisfaction, and productivity in Pakistan's South Waziristan Tribal District. The study provides a detailed picture of how workplace stress affects the performance and job happiness of healthcare employees in this location by delving into the specific issues they experience. Strong evidence favoring a correlation between these factors was discovered in the research. Employee performance was found to be significantly correlated with job stress, and job happiness was found to play a vital role in mediating this relationship. This study investigates the intricate relationships between key variables - workload, working environment, decision-making authority, and monetary rewards - in the healthcare sector of the South Waziristan Tribal District, Pakistan. These variables collectively influence the workplace experiences and overall job satisfaction of healthcare professionals, ultimately affecting their performance and the quality of healthcare services delivered. The study also provided new insight into the wide range of physical and mental pressures experienced by healthcare workers and their significant impact on their health. Stress management approaches, employee welfare programs, training, and equitable performance rating systems are among the many solutions proposed to meet these difficulties. The proposed changes are meant to improve the working conditions of healthcare professionals. The thesis also emphasizes the necessity for more studies in a variety of healthcare settings and geographical areas in order to fully address the complexities of occupational stress. In sum, this thesis provides insightful analysis and actionable suggestions for enhancing healthcare professionals' health and productivity, particularly in difficult settings like the South Waziristan Tribal District.